2007
DOI: 10.1016/j.maturitas.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum DHEAS levels are associated with a higher degree of physical disability and depressive symptoms in middle-aged to older African American women

Abstract: Background-Changes in androgen levels and associations with chronic disease, physical and neuropsychological function and disability in women over the middle to later years of life are not well understood and have not been extensively studied in African-American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 45 publications
(49 reference statements)
3
56
0
4
Order By: Relevance
“…A recent longitudinal study has indicated that higher testosterone levels may contribute more severe depressive symptoms in women during the menopausal transition (21). On the other hand, lower DHEA-S level has been shown to be associated with degree of depressive symptoms in women aged 49-65 years (15). Several studies have shown a significant association of low DHEA-S level with the presence of depressive symptoms in older women (20, 22, 23), while discordant results were obtained in other studies (24, 25).…”
Section: ) Depressionmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent longitudinal study has indicated that higher testosterone levels may contribute more severe depressive symptoms in women during the menopausal transition (21). On the other hand, lower DHEA-S level has been shown to be associated with degree of depressive symptoms in women aged 49-65 years (15). Several studies have shown a significant association of low DHEA-S level with the presence of depressive symptoms in older women (20, 22, 23), while discordant results were obtained in other studies (24, 25).…”
Section: ) Depressionmentioning
confidence: 87%
“…On the other hand, DHEA-S showed a modest association with physical functioning (16) and an inverse association with degree of physical disability in women (15). Bell et al reported that DHEA-S level was associated with greater vitality in premenopausal women, while both testosterone and DHEA-S did not make a contribution to well-being in postmenopausal women (17).…”
Section: ) Physical Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Большой объем данных был собран при обсле-довании пациентов с помощью спирометрической клас-сификации GOLD. Было выявлено, что при ухудшении показателей ограничения воздушного потока наблюда-ется увеличение риска обострений, госпитализации и смерти [3]. В последние десятилетия выполнены исследо-вания, по результатам которых существенно углубилось понимание патогенеза ХОБЛ и расширились терапевти-ческие возможности.…”
unclassified
“…При этом ДГЭА-С считают циркулирующим депо для регенерации ДГЭА. ДГЭА обладает слабым ан-дрогенным эффектом, является предшественником в си-стеме синтеза половых стероидов -андрогенов -тестосте-рона и андростендиона и эстрогенов -эстрадиола и эст- [3] и тяже-лая обструкция дыхательных путей, гипоксемия и гипер-капния. Дегидроэпиандростерон (DHEA) рассматрива-ется как важный иммуномодулирующий и противовоспа-лительный гормон.…”
unclassified